Game theoretic treatments for the differentiation of functional roles in the transition to multicellularity. (21st April 2016) - Tudge, S.J.; Watson, R.A.; Brede, M.
Abstract: Multicellular organisms are characterised by role specialisation, brought about by the epigenetic differentiation of their constituent parts. Conventional game theoretic studies of cooperation do not account for this division of labour, nor do they allow for the possibility of the plastic expression of phenotype. We address these issues by extending the notion of cooperative dilemmas to account for such interaction in which heterogeneous roles are advantageous and present an extended dynamical model of selection that allows for the possibility of conditional expression of phenotype. We use these models to investigate systematically when selection will favour an adaptive diversification of roles. We argue that such extensions to models and concepts are necessary to understand the origins of multicellularity and development. Abstract : Highlights: We demonstrate the shortcoming of conventional "Dawesian" cooperative dilemmas. We define a new type of evolutionary game called division of labour games. We show that assortment is insufficient for cooperation to evolove in such cases. We show that there exist two increasing levels of fitness in such games. We argue that these models shed valuable light on important biological processes.